Panics - Molinard, Barbara, 1921-1986 (The Feminist Press, 2022)
"A collection of thirteen short stories about sickness, death, mental illness, and control by French author Barbara Molinard (1921-1986), who destroyed much of her writing while still alive"-- Provided by publisher.
First published in French as Viens by Éditions Mercure de France in 1969.
Keywords: Molinard, Barbara, -- 1921-1986 -- Translations into English.; FICTION.; Short stories, French; short stories.; Short stories.; Nouvelles.